Types And Function Of Code Switching Found In Cinta Laura’s Utterance In Selected Youtube Video - Florianus Ibar; I Made Iwan Indrawan Jendra; Ni Made Verayanti Utami (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Abstract The purpose of this study is to illustrate the types and functions of code switching presented in Cinta Laura Kiehl's YouTube video. In the collection of data, the non-participatory method of observation Sugiyono was introduced (2009:15). Hoffman's theory (1996) is referred to in the study of data in order to analyze the forms of code switching, and Gumperz's theory (1982) is referred to in order to analyse the functions of code switching. It is done formally and informally to show the product of the analysis. The writer finds three types of code switching after analysing the results. There are intra-sentential 8 data, inter-sentential 2 data and emblematic switching is do not found data related. In the meantime, code switching has four functions; personalization versus objectification, reiteration, interjection, message qualification. This implies that there are two functions in the data that do not appear; quotation and addressee specification, since the utterance by Cinta Laura Kiehl never quote the opinions of other people or switch to direct the message to one or more potential addresses. Abstrak Tujuan dari peneltian ini adalah untuk menggambarkan tipe dan fungsi alih kode yang disajikan dalam vidio Youtube Cinta Laura Kiehl. Dalam pengumpulan data diperkenalkan metode observasi non partisipatif Sugiyono (2009: 15). Teori Hoffman (1996) digunakan dalam studi data untuk menganalisis bentuk alih kode, teori Gumperz (1982) digunakan untuk menganalisis fungsi alih kode. Ini di lakukan secara formal dan informal untuk menunjukan produk analisis. Penulis menemukan tiga jenis alih kode setelah menganalisis hasilnya. Data intra-sentential terdapat 8 data, data inter-sentential 2 dan switching simbolik tidak ditemukan data terkait. Semetara itu, alih kode memiliki emapat fungsi; Personalisasi versus objektifikasi, pengulangan interjeksi, kualifikasi pesan. Ini menyiratkan bahwa ada dua fungsi dalam data yang tidak muncul; Kutipan dan spesifikasi penerima, karena ucapan Cinta Laura Kiehl tidak pernah mengutip pendapat orang lain atau beralih untuk mengarahkan pesan ke sautu atau beberapa alamat potensial.